The 2020 Foreign Investment Law of China. Confucianism and New Challenges for Social Development (Contemporary Central & East European Law, 2020)
On January 1, 2020 the new Foreign Investment Law of the People’s Republic of China (中华人民共和国外商投资法) entered into force to promote investments in China. The aim of the law is to foster cross border investments. This law was passed on March 15, 2019 by the National People’s Congress. The Chinese FDI legal framework is composed of a set of laws and regulations that are dynamically shaping the economic reality. What are the possible tensions between the new law and the complex system of values in China? Is the new law an agent of implementing de facto social development? In summary, the results show that there is a complex relationship between FDI and social development in China. The new Chinese law might be an inspirational source of non-European legal tradition for Central Europeans.